Mimetic de-commemoration the fate of Soviet war memorials in Eastern Europe in 2022-2023 - Gabowitsch, Mischa 1977- (2024)
Some observers have claimed that Soviet monuments, and in particular war memorials, are coming down "across Europe" in response to the Russian full-scale invasion of Ukraine. Soviet war memorials have indeed been removed in large numbers in 2022–2023, even though previous waves of decommunisation had often spared them. However, the geography of this new strong iconoclasm is limited to Poland, Estonia, Latvia, Lithuania and some regions of Ukraine, in addition to one case in Czechia and one in Bulgaria. This article analyses the new bureaucracies of iconoclasm, noting that they first emerged in Poland and then spread to new countries in a mimetic process. The article then reviews the actors and logics of monument destruction and protection. Whereas (mostly right-wing) governments and activists have spearheaded the removal of war memorials, the case to recontextualise monuments instead of removing them was primarily made by historians, art historians and heritage experts. The article dwells in particular on the ways in which Soviet World War II memorials have been appropriated and domesticated by local residents, gaining new meanings that go beyond their original ideological messages. It argues that de-commemoration, like commemoration, should be a complex process involving all those with a connection to the monument and what it memorialises, and that the top-down removal campaigns of 2022–2023 have largely eschewed democratic deliberation